Treatment of temporomandibular joint trauma following odontectomy - Ruspita, Intan; Dipoyono, Haryo Mustiko (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Temporomandibular Joint Disorder (TMD) is a non-dental musculoskeletal disorder that has a complex and multifactorial etiology. The most frequent symptoms are pain in the masticatory muscles, in front of the ears, and in the temporomandibular joint (TMJ); this disorder can also be accompanied by clicking sounds and locking. This study aimed to present a case report of temporomandibular joint trauma following odontectomy. A 22-year-old patient came with some complaints, namely pain in the TMJ, a clicking sound when opening and closing the mouth, and limited mouth opening. The symptoms started when the patient underwent odontectomy on all the four third molars, causing tightness around the jaw, pain, and clicking. However, she did not seek any treatment for these conditions until the pain became worse and disturbed her activities. The patient had to deal with limited mouth opening and severe migraines up to twice a day. During an examination, the patient was able to open her mouth without pain only 25 mm in width, with a maximum mouth opening of 35 mm. The therapy was done by constructing a 4-mm stabilization splint and educating the patient on how to reduce the pain. In fact, 2 months after the treatment and the use of stabilization splints, her complaints of TMJ pain and clicking sounds decreased, her mouth opening increased, and the migraines never came back. In this case, non-invasive treatment as the first-line therapy in patients with disc displacement with reduction and arthralgia can reduce the joint pain symptoms, and some of the symptoms have even disappeared.